Affective Engagement of Higher Education Students in an Online Course - Wajeeh Daher; Kifaya Sabbah; Maysa Abuzant (Ital Publication, 2021)
The present research studies the factors that have impacted the affective engagement of university students in an educational online course. It examines how the type of interaction (learner-learner, learner-instructor, and learner-content) and the type of engagement (behavioural, cognitive and affective) have influenced the affective engagement of the students in the online course. Nineteen university students majoring in teaching mathematics, who were enrolled in the course Mathematics Teaching Methods, participated in the present research. Two data collection tools were used: semi-structured interviews and reflections. To analyse the texts resulting from the interviews and reflections, inductive and deductive qualitative content analysis was used. The research results indicated that university students have experienced more positive than negative affective engagement in the three communicational channels used in this course to facilitate online learning, which were: synchronous lectures, forums and assignments. The results also indicated that these three types of interaction have positively influenced students’ affective engagement in the three channels, with that influence being different from one channel to the other based on the interaction type taking place. We suggest that specific types of engagement need to be attended to for positive affect to occur. Doi: 10.28991/esj-2021-01296 Full Text: PDF